(untitled) (Malaysian Management Journal, 2002)
Previous research have looked at the relationship between sensitivity and satisfaction, and between group size and satisfaction. However there appears to be no reported studies that have investigated the interacting effects of group size on the relationship between sensitivity and satisfaction. Data from 257 shop floor workers in a light manufacturing plant in the U.K were collected and analysed. Group size was significantly negatively related to satisfaction with co-workers. Statistical tests of hierarchical multiple regression were used to determine the significance of the interaction terms (sensitivity x group size) on pay and co-worker satisfaction. Support for both hypotheses were obtained. Results suggested that group size significantly moderated the relationship between sensitivity and pay satisfaction, and the relationship between sensitivity and co-worker satisfaction. Linear regression plots showed that the relationship between sensitivity and satisfaction (pay and co-worker) were negative in large groups but positive in small groups.